Connecting Binomial and Black-Scholes Option Pricing Models: A Spreadsheet-Based Illustration - Yi Feng; Clarence C. Y. Kwan (Spreadsheets in Education, 2012)
The Black-Scholes option pricing model is part of the modern financial curriculum, even at the introductory level. However, as the derivation of the model, which requires advanced mathematical tools, is well beyond the scope of standard finance textbooks, the model has remained a great, but mysterious, recipe for many students. This paper illustrates, from a pedagogic perspective, how a simple binomial model, which converges to the Black-Scholes formula, can capture the economic insight in the original derivation. Microsoft ExcelTM plays an important pedagogic role in connecting the two models. The interactivity as provided by scroll bars, in conjunction with Excel's graphical features, will allow students to visualize the impacts of individual input parameters on option pricing.